A chemical redox reaction to generate rock salt-type materials: the case of Na3V2O5. Issue 9 (8th January 2018) - Adamczyk, E.; Anger, E.; Freire, M.; Pralong, V.
Abstract : Chemical redox reactions are extremely efficient to prepare fully reduced or oxidized phases that are formed during the topotactic insertion/extraction of alkaline ions. Moreover, these phases show new ordered or disordered Rock Salt type structures. Abstract : Chemical redox reactions are extremely efficient to prepare fully reduced or oxidized phases that are formed during the topotactic insertion/extraction of alkaline ions. Herein, we report these reactions and discuss the possibility to generate new ordered or disordered rock salt-type structures depending on the structure of the mother phase. We have shown that a disordered rock salt-type structure is formed when the transition element is located at the tetrahedral site, as exemplified by the formation of Na3 V2 O5 upon chemical reduction of V2 O5 .